Through the Lens of Accountability: Body-Worn Cameras in Police Operations at Pampanga Police Provincial Office - Mercado, Hamilton A. (Future Science / FSH-PH Publications, 2024)
This study evaluates the compliance of the Pampanga Provincial Police Office with the use of body-worn cameras and alternative recording devices during police operations in the province Pampanga and examines the severity of problems encountered in their use. Specifically, it assesses compliance in terms of procedural fairness, police performance, data protocols, privacy concerns, and camera benefit while investigating the relationship between compliance levels and encountered problems. It hypothesizes that higher compliance levels are associated with fewer operational problems and that certain areas, such as data protocols and privacy, may present greater challenges. A descriptive correlational design was used, employing structured questionnaires to gather data from 200 respondents, including police officers and community members. Key findings indicate a very high compliance level in using Body-Worn Cameras and Alternative Recording Devices (Mean = 3.49), but also highlight significant challenges, with an overall severity rating of problems as high (Mean = 2.81). Correlational analysis suggests a moderate positive relationship between perceived compliance and the severity of problems faced. The study recommends tailored training, procedural adjustments, and improved data management and privacy measures to address these challenges. Limitations of the study include potential biases in respondent perceptions and constraints in generalizing findings to other regions. Policymakers are urged to enhance transparency, accountability, and public trust in police practices to foster a safer community environment in Pampanga Province.